Genetic Characterization and Phylogenetic Analysis of Babesia bigemina Isolates in Cattle from South Africa Based on BgRAP-1, BgAMA-1 and BgβTUB Genes - Phillip Senzo Mtshali; Moses Sibusiso Mtshali (Biology)
Babesia bigemina is one of the most important etiological agents of bovine babesiosis, a tick-borne disease posing a major threat in the livestock industry globally, including South Africa. Despite the huge economic impact of cattle babesiosis in South Africa, antigenic variation observed among B. bigemina strains worldwide has impeded the successful development of a single vaccine with the potential to eliminate the disease. As such, there is still a dearth of information regarding the conservation of B. bigemina genes encoding functionally important proteins that play a crucial role during the invasion of bovine erythrocytes by merozoites. Fifty blood samples previously collected from cattle in eight provinces of South Africa were genetically tested for the presence of B. bigemina DNA fragments using four nested PCR-based assays. The genes targeted coded for SpeI-AvaI restriction fragment, rhoptry-associated protein 1 (BgRAP-1), apical membrane antigen 1 (BgAMA-1) and β-tubulin (BgβTUB). PCR-generated fragments of randomly selected samples were sequenced. BLAST searches in GenBank were performed with newly determined sequences to search for homologous sequences. Neighbor-joining phylogenies were inferred from aligned, contiguous sequences of BgRAP-1, BgAMA-1 and BgβTUB genes. Nested PCR assays generated single fragments of 170 bp, 472 bp, 765 bp and 302 bp for SpeI-AvaI, BgRAP-1, BgAMA-1 and BgβTUB fragments, respectively. Of the 50 bovine samples tested by nested PCR, 82% (42/50; 95% CI = 69.2–90.2%), 68% (34/50; 95% CI = 54.2–79.2%), 50% (25/50; 95% CI = 36.6–63.4%) and 46% (23/50; 95% CI = 33.0–59.6%) possessed B. bigemina-specific SpeI-AvaI, BgRAP-1, BgAMA-1 and BgβTUB DNA fragments, respectively. The BgRAP-1, BgAMA-1 and BgβTUB sequences of South African B. bigemina isolates shared 98–100% similarity with previously reported sequences of strains originating from cattle in countries other than South Africa. The high genetic conservation observed among geographical isolates of B. bigemina suggests the conserved functional role of BgRAP-1 and BgAMA-1 proteins as potential candidates that could be incorporated in recombinant subunit vaccines.